Grain size effect on radiation tolerance of nanocrystalline Mo. (October 2016) - Cheng, G.M.; Xu, W.Z.; Wang, Y.Q.; Misra, A.; Zhu, Y.T.
Abstract: We report a significant grain size effect on radiation tolerance of nanocrystalline Mo under He ion irradiation. Irradiation-induced dislocation loops mainly contribute to the irradiation-induced hardening of Mo films with grain size of > 90 nm, while few such loops in those with grain size of < 90 nm. The hardness increment after irradiation decreases with decreasing the grain size, and approaches zero at the grain size of 25 nm. Also, the size and the density of irradiation-induced He bubbles decrease as the grain size decreases. This observation provides direct evidence that nanocrystalline body-centered-cubic metals have greater radiation tolerance than their ultra-fine-grained or coarse-grained counterparts. Graphical abstract: